MEDIATING EFFECTS OF TEAM TRUST AND TEAM INTERACTIVE BEHAVIOR ON RELATIONSHIP BETWEEN FLEXIBLE LEADERSHIP AND INNOVATION TEAM EFFECTIVENESS IN UNIVERSITIES IN GREATER BAY AREA - Hongwei, Zhang; Pruettikul, sataporn; Moonmuang, Sukhum (วารสารนิสิตวัง, 2025)
The objectives of this research were: (1) to study the components of team trust, team interactive behavior, flexible leadership and innovation team effectiveness. (2) to develop a model of mediating effects of team trust and team interactive behavior on the relationship between flexible leadership and innovation team effectiveness in universities, and (3) to verify the effect of team trust, team interactive behavior and flexible leadership effect on the innovation team effectiveness in Universities in Greater Bay Area. The population of this research were 4,883 teachers working in universities in the Guangdong Hong Kong Macao Greater Bay Area, Republic of China. The sample was determined by G*power, total 539 teachers and were obtained by proportional stratified random sampling method. The statistical for data analysis includes Confirmatory Factor Analysis and Structural Equation Modeling. The research found that : (1) The flexible leadership was seven components include; Planning ability, Adaptability, guidance ability, control ability, caring ability, resilience ability and growth ability. The Innovation team effectiveness was three components include; innovation task performance, cooperation satisfaction and team growth. The team trust was two components include; cognitive trust and emotional trust, and the team interactive behavior was four components include; team support, team communication, team work and knowledge sharing; (2) The mediating effects of team trust and team interactive behavior on relationship between flexible leadership and innovation team effectiveness in the Greater Bay Area fit well with empirical data. And (3) Flexible leadership, Team trust and team innovative behavior had a positive effect on the innovation team effectiveness. In addition, the Flexible leadership could be positive indirect effect on team innovative effectiveness through team trust and team interactive behavior, which were as mediation effect. So, in organization should be promoting all of them togethers for innovation team effectiveness improvement.